2015
DOI: 10.1109/jphotov.2014.2382975
|View full text |Cite
|
Sign up to set email alerts
|

Ion Implantation for Poly-Si Passivated Back-Junction Back-Contacted Solar Cells

Abstract: We study ion implantation for patterned doping of back-junction back-contacted solar cells with polycrystallinemonocrystalline Si junctions. In particular, we investigate the concept of counterdoping, that is, a process of first implanting a blanket emitter and afterward locally overcompensating the emitter by applying masked ion implantation for the back surface field (BSF) species. On planar test structures with blanket implants, we measure saturation current densities J 0 ,p oly of down to 1.0 ± 1.1 fA/cm 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(66 citation statements)
references
References 19 publications
6
60
0
Order By: Relevance
“…Some researchers deposit an in-situ doped amorphous or polycrystalline silicon layer by PECVD using phosphine and silane [17]. Alternatively, ion implantation followed by a thermal step can be used to dope intrinsic polysilicon [18,19]. Recently, a related approach labelled tunnel oxide passivated contact (TOPCon), based on an in-situ phosphorus doped amorphous silicon layer, subjected to a heat treatment, has achieved an open circuit voltage of 700 mV and an efficiency of 24% without degrading the fill factor (80%) [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers deposit an in-situ doped amorphous or polycrystalline silicon layer by PECVD using phosphine and silane [17]. Alternatively, ion implantation followed by a thermal step can be used to dope intrinsic polysilicon [18,19]. Recently, a related approach labelled tunnel oxide passivated contact (TOPCon), based on an in-situ phosphorus doped amorphous silicon layer, subjected to a heat treatment, has achieved an open circuit voltage of 700 mV and an efficiency of 24% without degrading the fill factor (80%) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a related approach labelled tunnel oxide passivated contact (TOPCon), based on an in-situ phosphorus doped amorphous silicon layer, subjected to a heat treatment, has achieved an open circuit voltage of 700 mV and an efficiency of 24% without degrading the fill factor (80%) [17]. Other studies of ion implanted and thermally activated polysilicon layers have demonstrated very low recombination current densities J 0 ∼1 fA/cm 2 for n þ polysilicon and ∼4.4 fA/cm 2 for p þ polysilicon [19,20], which shows the great potential of doped polysilicon as a passivated contact for solar cells. In addition to in-situ doping or ion implantation, conventional thermal diffusion can be used to dope the polysilicon [13], with the added advantage of being a well-established process in the solar cell industry.…”
Section: Introductionmentioning
confidence: 99%
“…For IBC architectures, surface passivation is achieved by introducing a doped region (FSF or FFE) in combination with a proper passivation stack [19,20]. In case of relatively low surface defect density, lightly-doped FSFs can offer enough band-bending (potential barrier at high-low junction) to prevent minority carrier recombination on the front surface [35][36][37][38][39] without dramatically increasing recombination losses in the doped region.…”
Section: Strategy For Front Side Passivationmentioning
confidence: 99%
“…The usage of ion-implanted polySi as potential passivating contacts for c-Si solar cells has been also recently reported. 7,8 In such contributions, the authors have calculated the iV OC and the pFF based on dark-saturation current measured with Quasi-Steady State Photoconductance (QSSPC) 7,8 or have reported the potential V OC and FF of an IBC solar-cell device with polySi passivating contacts based on the measured V OC and FF of the front back contacted solar cell structures. 9 In this letter, we show the development of ion-implanted polySi n-type and p-type passivating contacts and their implementation at the back side of IBC solar cells.…”
mentioning
confidence: 99%
“…The physics behind this effect is not yet well understood, we suggest the following explanations: (1) The c-Si at the interface between c-Si bulk and the NAOS/polySi becomes a heavily doped n þþ region due to the P in-diffusion inducing a strong increase of the Auger recombination rate; (2) this heavily doped region also dis-functions the carrier selectivity of the passivating contacts due to insufficient quasi Fermi level separation at bulk/polySi interface; and (3) the pin-holes in the tunneling oxide layer due to the high temperature process may also increase the oxide layer interface trap density, therefore, increase the SiO 2 /cSi interface recombination, which is considered as the dominating recombination mechanism. 7,12 All in all, the concurrent combination of these effects may enhance carrier recombination. To clarify the mechanism, further studies are required.…”
mentioning
confidence: 99%